Exploring the influences of surrounding environments on students' habits - Bakri, Fitriyani; Halim, Abd; Hasbi, Muhammad; Halim, Nur Mutmainna (EduLite: Journal of English Education, Literature and Culture, 2024)
Acknowledging that students are intricately woven into diverse physical, social, and cultural fabric forms, this study aims to explore the multifaceted impact of the surrounding environment on the habits of students. This study employed a correlational research design to investigate the relationship between the family environment (X1) and the school environment (X2) on students' habits at IBC School Makassar (Y). The study conducted a comprehensive approach encompassing academic and non-academic habits to provide a nuanced understanding of the intricate. Through a correlational design, the study analyses various environmental factors, including home environment and school environment. By analyzing the impact of these variables on the routines of students, the study seeks to discern recurring trends and associations that facilitate the formation and reinforcement of particular conduct. The population of this study was students at IBC School Makassar in the academic year of 2023/2024. The researchers selected 1 class of 10 students as samples of the study. The data was collected through the distribution of questionnaires regarding the students' habits, familial environment, and school environment. According to the research findings, the assertion that family and school environments have a one hundred percent impact on students' behaviors at IBC School Makassar is a strong statement. Both family and school environments play pivotal roles in shaping student behavior. The interplay between these two environments is crucial for the holistic development of students.